Financially Savvy and Character-Building Generation: Implementation of Islamic Human Resource Management and Finance at Sangkhom Islam Wittaya School, Thailand - Yahya, Wahyudin; K., M. Yusuf; Anwar, Anwar; Badollahi, Ismail; Hak, Nasrul (Journal of Community Service and Society Empowerment, 2025)
Improving financial literacy and character building based on Islamic values is an urgent need in facing global challenges, especially among the younger generation. This study implements human resource management and Islamic finance at Sangkhom Islam Wittaya School, Thailand, through a participatory education-based community service programme. The activity began with a needs analysis to map the level of understanding of students and teachers regarding HR and financial management. Next, a training module was developed that combined the concepts of HR management, Islamic financial literacy, and Islamic character values. Training and mentoring in simple financial management practices were provided to instil skills in planning, recording, and managing funds in accordance with Islamic principles. The results of the programme showed a significant increase in students understanding of Islamic financial management, human resource management, and a positive attitude towards the application of the values of honesty, responsibility, and discipline. The long-term impact of this programme is expected to create a generation that is financially literate, has good character, and is competitive, while also being able to maintain the integrity of Islamic values. This implementation can serve as a model of practical and relevant Islamic financial literacy for Islamic-based schools in the Southeast Asian region